Efeitos do tratamento crônico com tamoxifeno e quimioterapia sobre marcadores de risco cardiovascular em mulheres com câncer de mama - Romero, Walckiria Garcia (2012)
The present study was aimed to assess the role of tamoxifen in risk predictors for development of heart diseases, such as the C-reactive protein (CRP), apolipoproteins A-1 (Apo-A), apolipoproteins B-100 (Apo-B), B-type natriuretic peptide (BNP) and the impacts of echocardiograms, particularly the left ventricular ejection fraction (LVEF), in women undergoing chemotherapy treatment for breast cancer. Sixty women with breast cancer were evaluated over a 12-month period and were divided into the following groups: group that received only chemotherapy (QUIMIO) n=23; group that received chemotherapy and tamoxifen (QUIMIO+TAM) n=21; group that received only tamoxifen (TAM) n=16. The plasma levels of CRP were assessed at the beginning of treatment (T0), in the 3rd month (T3), 6th month (T6) and 12th month (T12) of treatment. The levels of Apo-A, Apo-B and pro-BNP were assessed in the T0, T6 and T12. Echocardiograms were performed in the T0 and T12. Increased plasma concentrations of CRP were observed in the QUIMIO and QUIMIO+TAM groups, in the 3rd (10.85 ± 0.02 mg/dL; 10.81 ± 2.97mg/dL) and 6th months of treatment (12.5 ± 1.95 mg/dL; 12.36 ± 2.64 mg/dL). However, at the end of the 12th month of treatment, the QUIMIO+TAM and TAM groups showed significant (p<0,01) reduction in the CRP (1.04 ± 0.38 mg/dL; 1.04 ± 0.38 mg/dL), and Apo-B values (94.3 ± 9.3 mg/dL; 96.3 ± 5 mg/dL), and in the Apo-B/Apo-A ratio (0.53 ± 0.01; 0.52 ± 0.01mg/dL), with significant increase in serum levels of Apo-A (179.5 ± 7.64; 185.1 ± 7.87 mg/dL, p<0,01). These results were not observed in the group that was given chemotherapy only (QUIMIO). The plasma values of pro-BNP were higher in the QUIMIO, QUIMIO+TAM groups in T6 (69,06 ± 11,7 pg/ml; 67,35 ± 11,9 pg/mL, p<0,01, respectively), when compared to the beginning of treatment (8,98 ± 2,1 pg/mL; 9,48 ± 1,79 pg/mL). Group QUIMIO+TAM, in turn, showed significant reduction of this peptide in T12, with values similar to those of the TAM group (11,39 ± 2,74; 8,35 ± 1,66 pg/mL, p<0,01), with the QUIMIO group maintaining high levels of pro-BNP (42,35 ± 12,9 pg/mL). Regarding LVEF, the QUIMIO group showed a significant impairment of cardiac performance (63,3 ± 4,3%, p< 0,01), whereas the QUIMIO+TAM and TAM groups maintained values similar to those observed in the beginning of treatment (76,2 ± 3,7%; 75,6 ± 4,1% vs. 73,7 ± 4,2%; 76,8 ± 4,82%, respectively). Therefore, the use of tamoxifen significantly reduces the presence of risk markers for CVD and improves the ventricular function in women after 6 months of chemotherapy for treatment the breast cancer.